High ionic-conducting Li-argyrodites synthesized using a simple and economic liquid-phase approach and their application in all solid-state-lithium batteries. (November 2021) - Subramanian, Yuvaraj; Rajagopal, Rajesh; Ryu, Kwang-Sun
Abstract: We develop a new solution synthesis strategy for producing high ionic-conducting sulfide solid electrolyte using ethylenediamine (EDA) solvent. Here, we follow three simple steps: dissolve the precursor in ethylenediamine solvent to form the clear solution, then removing a solvent at 180 °C followed by heat treatment. The prepared Li5.5 PS4.5 Cl1.5 electrolyte demonstrated the high ionic conductivity of 2.87 mS cm −1 at 25 °C. Further, fabricated solid battery using optimized electrolyte exhibited a high initial discharge capacity of 175.7 mAh g −1 at 0.1 C rate. Moreover, the synthesis technique is a convenient and quick process, thus facilitating mass production of solid electrolytes. Graphical abstract: Image, graphical abstract